Reproductive system cancer in females of the Tyva Republic. Epidemiological characteristics - G. A. Kononova; L. D. Zhuikova; O. A. Ananina; L. A. Kolomiets; L. V. Pikalova; A. S. Zhuikova (Сибирский онкологический журнал, 2024)
Background. The incidence of female reproductive system cancer, including breast, cervical, ovarian and uterine cancers, is steadily increasing, and therefore it is advisable to conduct an epidemiological analysis and assess the quality of medical care. The purpose of the study was to analyze the epidemiological characteristics of reproductive system cancer in females of the Tyva Republic. Material and Methods. The reporting forms № 7 “Cancer incidence in the Tyva Republic” for 2013–2022 were used. Age-standardized incidence rates were calculated using the “Oncostat” program, and cancer care quality was assessed using “Cancer Care Indicators” program. Results. Reproductive system cancer in the Tyva Republic accounted for 46.3 % of all malignant neoplasms in females during 2013–2022. In 2022, breast cancer was the most common cancer (16.2 %) followed by cervical cancer (13.7 %), ovarian cancer (6.7 %), and uterine cancer (4.0 %). During the study period, none of these cancers showed a statistically significant increase in agestandardized incidence rates (AS R). In 2022, age-standardized incidence rates in the Tyva Republic were higher than those in the Siberian Federal District for cervical cancer (27.5 ± 3.7 vs 16.3 ± 0.4 0/0000) and for ovarian cancer (14.1 ± 2.8 vs 12.7 ± 0.3 0/0000), but lower for breast cancer (32.4 ± 4.1 vs 58.7 ± 0.6 0/0000) and uterine cancer (8.6 ± 2.2 vs 19.7 ± 0.4 0/0000). Overall, cancer care quality indicators for reproductive system cancers had improved. Active detection increased from 22.0 to 29.8 %, p=0.039 (in the Siberian Federal District: from 27.6 to 37.2 %, p=0.001). The detection rate at I–II stages increased from 53.7 to 75.2 %, p=0.004 (in the Siberian Federal District: from 63.0 to 71.3 %, p=0.001). The percentage of advanced stages decreased from 37.4 % to 15.5 %, p=0.001 (from 27.4 % to 23.1 % in the Siberian Federal District, p=0.013). The oneyear mortality rates also decreased from 19.0 to 5.4 %, p=0.013 (in the Siberian Federal District: from 11.8 to 8.5 %, р<0.001). The high incidence of cervical cancer, the absence of noticeable optimal changes in the early detection and the high prevalence of HPV infection among the female population of the Tyva Republic indicate the relevance of mass HPV testing as a part of secondary cancer prevention. Conclusion. The high incidence of female reproductive system cancer and the current status of reproductive cancer care in the Republic of Tyva dictate the need to strengthen primary, secondary and tertiary cancer prevention.